2018
DOI: 10.1017/s0007114518000417
|View full text |Cite
|
Sign up to set email alerts
|

Excess free fructose, high-fructose corn syrup and adult asthma: the Framingham Offspring Cohort

Abstract: There is growing evidence that intakes of high-fructose corn syrup (HFCS), HFCS-sweetened soda, fruit drinks and apple juice - a high-fructose 100 % juice - are associated with asthma, possibly because of the high fructose:glucose ratios and underlying fructose malabsorption, which may contribute to enteral formation of pro-inflammatory advanced glycation end products, which bind receptors that are mediators of asthma. Cox proportional hazards models were used to assess associations between intakes of these be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 58 publications
4
46
4
Order By: Relevance
“…Special Considerations: Sugar-Sweetened Beverages Sugarsweetened beverages (SSBs) are a nutritional component that has received increasing attention over the last decade. SSBs are associated with asthma prevalence and morbidity, independent of obesity, in children and adults in cross-sectional and prospective studies [101][102][103][104][105][106][107][108]. In the prospective Framingham Offspring Cohort study, the consumption of SSBs with excess fructose content was associated with a dose-dependent increase in asthma risk for adults (HR, 1.89; 95%CI 1.36-2.62 for 5-7 servings/week) when adjusted for demographics, BMI, smoking, and type II diabetes [102••].…”
Section: Materials Circumstances: Food Insecurity and Nutritionmentioning
confidence: 99%
“…Special Considerations: Sugar-Sweetened Beverages Sugarsweetened beverages (SSBs) are a nutritional component that has received increasing attention over the last decade. SSBs are associated with asthma prevalence and morbidity, independent of obesity, in children and adults in cross-sectional and prospective studies [101][102][103][104][105][106][107][108]. In the prospective Framingham Offspring Cohort study, the consumption of SSBs with excess fructose content was associated with a dose-dependent increase in asthma risk for adults (HR, 1.89; 95%CI 1.36-2.62 for 5-7 servings/week) when adjusted for demographics, BMI, smoking, and type II diabetes [102••].…”
Section: Materials Circumstances: Food Insecurity and Nutritionmentioning
confidence: 99%
“…Table 1 shows the main characteristics of all 19 studies included in our review. Twelve studies reported on childhood exposure to soft drinks,5 11 12 14 24–31 six studies on adulthood exposure to soft drinks13 15 16 32–34 and two studies on maternal consumption of soft drinks and asthma in the offspring 31 35. Three studies were cohort studies16 31 35 and 16 were cross-sectional studies 5 12–15 24 26–30 32–34 36 37.…”
Section: Resultsmentioning
confidence: 99%
“…Although not confirmed, there were several theories proposed which suggest the importance of soft drink consumption in the development of asthma. For example, sugar (or specifically fructose) activates an inflammatory pathway16; additive substances trigger symptoms12 or soft drinks leading to overweight would serve as a mediator 14. Identification of preventable risk factors is of paramount importance to guide public health prevention measures to reduce the burden of asthma 2 4.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, two cross-sectional studies [28,29] and one longitudinal study [30] have been published regarding the role of SSB on asthma outcomes, and all three reported a positive association. In our opinion, the handling of confounding and effect modification is problematic in most epidemiological studies of the diet-asthma association.…”
Section: Sugar-sweetened Beverages Consumptionmentioning
confidence: 99%
“…Indeed, given the established evidence that links SSB to obesity and that links obesity to asthma, it is likely that obesity act as a potential mediator in the SSB-asthma association (and not a confounder). Whereas the analyses performed by Shi et al and DeChristopher et al were adjusted for obesity [28,30], Park et al performed a stratified analysis for obesity and, interestingly, reported that frequent SSB consumption was associated with current asthma among non-obese adults only [29]. Other conditions could also lie in the causal pathway between SSB intake and asthma symptoms, such as gastroesophageal reflux disease (GERD) which is closely associated with SSB intake [31] and greater asthma symptoms [32], but can also exhibit complex temporal association with obesity.…”
Section: Sugar-sweetened Beverages Consumptionmentioning
confidence: 99%